2010
DOI: 10.1101/lm.1576810
|View full text |Cite
|
Sign up to set email alerts
|

The infralimbic cortex regulates the consolidation of extinction after cocaine self-administration

Abstract: The infralimbic cortex (IL) regulates the consolidation of extinction learning for fear conditioning. Whether the IL influences the consolidation of extinction learning for cocaine self-administration is unknown. To address this issue, male Sprague -Dawley rats underwent 2 wk of cocaine self-administration followed by extinction training. On the first 5 d of extinction, rats underwent brief (15-or 30-min) extinction sessions and received intra-IL microinjections immediately after each extinction session. On da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
144
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(157 citation statements)
references
References 40 publications
12
144
1
Order By: Relevance
“…This result is difficult to explain solely in terms of enhanced consolidation and strongly suggests that NE signaling can also enhance extinction learning. This is consistent with previous demonstrations that pre-training but not posttraining b-adrenergic receptor blockade can impair extinction (Mueller et al, 2008;LaLumiere et al, 2010). Together, these results are most consistent with the view that NE can promote learning-related plasticity, but that the type of learning that is either enhanced or impaired will depend on the details of the experimental design.…”
Section: Learning Consolidation and Reconsolidationsupporting
confidence: 81%
See 3 more Smart Citations
“…This result is difficult to explain solely in terms of enhanced consolidation and strongly suggests that NE signaling can also enhance extinction learning. This is consistent with previous demonstrations that pre-training but not posttraining b-adrenergic receptor blockade can impair extinction (Mueller et al, 2008;LaLumiere et al, 2010). Together, these results are most consistent with the view that NE can promote learning-related plasticity, but that the type of learning that is either enhanced or impaired will depend on the details of the experimental design.…”
Section: Learning Consolidation and Reconsolidationsupporting
confidence: 81%
“…Importantly, many of these effects ultimately rely on action at the b-adrenergic receptors (Ferry et al, 1999;Roozendaal et al, 2002;Berlau and McGaugh, 2006;Mueller et al, 2008;LaLumiere et al, 2010). Thus, taken together with our propranolol results, it is likely that the results reported here with atomoxetine result from increases in synaptic NE levels that allow for greater potential activity at the b-adrenergic receptor.…”
Section: Receptor Specificitymentioning
confidence: 65%
See 2 more Smart Citations
“…Furthermore, it is well accepted that norepinephrine facilitates, rather than impedes, memory formation through b-receptor activation (McGaugh, 2000). Finally, research has demonstrated that propranolol impairs extinction learning (for review see Mueller and Cahill, 2010) in both aversive (Do-Monte et al, 2010;Merlo and Izquierdo, 1967;Mueller et al, 2008;Ouyang and Thomas, 2005) and appetitive paradigms (LaLumiere et al, 2010).…”
Section: Time In Chamber (Sec)mentioning
confidence: 99%